OKRES DWUDZIESTOLECIA MIĘDZYWOJENNEGO A ROZWÓJ NAUKI PRAWA RZYMSKIEGO W POLSCE - Czech-Jezierska, Bożena (Zeszyty Prawnicze, 2016)
The Period of the Interwar Period – The Development of Roman Law Studies Summary The interwar period was a historical stage that was full of events in a world of science. The scientific activity reflected patriotism at the time. The energy engaged by the Polish scholars in developing and popularizing all the fields of science seemed to be the energy engaged in rebuilding of Polish State. Despite the difficulties with building up a consistent legal system, the interwar period is said to be respectful to ancient legal culture and rules. Legal education and the place of Roman law in it were indicators of significant role of this science. At the same time they statued an excellent school of juridical thinking and introduction into the modern law. University education of jurists was held in the six universities in: Cracow, Lviv, Warsaw, Lublin, Vilnius and Poznan. Roman law was taught at these universities partucularly by: Stanisław Wróblewski, Ignacy Koschembahr- Łyskowski, Leon Piniński, Marceli Chlamtacz, Wacław Osuchowski, ks. Henryk Insadowski, Franciszek Bossowski, Włodzimierz Kozubski, Zygmunt Lisowski. Apart from teaching activity, Roman law specialists also developed scienitific initiative. The author described development of Roman law science and studies during the rebuilding of Polish statehood. Therefore she analysed the place of Roman law in the university legal education system and the tendencies of Roman law scholar’s studies to whom it owed the significant position of scientific discipline. This issue is still waiting for a complex description and analysis. This will help to investigate multidirectional character of Polish Roman law scientists studies during the interwar period and their contribution to the global Roman law studies. The interwar period was stage unusually rich in events in the word of science. The scientific activity became the word of the patriotism then, the energy put by Polish scholars into the development and popularizing all fields of science was an energy put into the reconstruction of you Polish. In spite of the difficulties building the consistent legal system up caused which, the period between wars was characteristic of a respect to principles of the legal culture. A legal education was one of her indicators, and in it – the place of the Roman law, constituting the excellent school of the legal thinking and leading into the contemporary law. University educating jurists was held then in six universities: in Cracow, Lviv, Warsaw, Lublin, Vilnius and Poznan. They laid the Roman law out there among others: Stanisław Wróblewski, Ignacy Koschembahr-Łyskowski, Leon Piniński, Marceli Chlamtacz, Wacław Osuchowski, rev. Henryk Insadowski, Franciszek Bossowski, Włodzimierz Kozubski, Zygmunt Lisowski. Apart from teaching activity specialists in Romance studies also developed the scientific initiative. The author described the development of the learning, including teachings, of Roman law in times of the reconstruction of the statehood. She analysed the place of the Roman law therefore in the university legal education and lines of enquiry of professors which the Roman law owed holding in the university item due to him of the scientific discipline to. This issue is waiting for a complex scientific description and analysis, that will help to investigate the multidirectional character of their interests and also the place of their scientific output in the global Roman studies.